Evaluating outcomes following assessment of idiopathic scoliosis - Onuoha, Kelechukwu; Obong, Udemeobong; Omokore, Olutomiwa; Kolawole, Dosunmu; Fafolahan, Abiola; Fadeyibi, Olatunbosun (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescent Idiopathic scoliosis (AIS) is the most common cause of three-dimensional deformities of the spine. To evaluate the prevalence, association between Cobbs angle and some independent variables such as age and sex of orthopedic patients at Babcock University Teaching Hospital, Ogun, South West, Nigeria. Methods: This was a retrospective epidemiological study of scoliosis patients seen between January 2019 to December 2021 at Babcock University Teaching Hospital, Ogun State. Data were obtained from patients medical records after due permission had been sought for and obtained from the hospital management. Results: The prevalence of scoliosis among the patients was 2.62% and females have higher rates of scoliosis as compared to the males. We also found out that majority of the patients were older than 18 years of age with a prevalence of 1.33% while the prevalence for early age was 1.29%. The most common Cobbs angle was 10-19°. Lower back pain (55.8%) was the major reason for showing up at the hospital. Out of all treatment options, the most offered was Physiotherapy and medications (48.1%). There was significant association between Cobbs angle and age (p<0.005). Conclusions: The prevalence of scoliosis among orthopedic patients at Babcock University Teaching Hospital, Ogun state was 2.62 %. Age was associated with Cobb’s angle.